142k views
0 votes
3(3y - 6) = 7y - 18 + Zy
The answer

User Bob Thule
by
5.1k points

2 Answers

5 votes

Answer: y= 0/-z+2

Explanation:

3(3y−6)=7y−18+zy

Step 1:

9y−18+−yz=yz+7y−18+−yz

−yz+9y−18=7y−18

Step 2:

−yz+9y−18+−7y=7y−18+−7y

−yz+2y−18=−18

Step 3:

−yz+2y−18+18=−18+18

−yz+2y=0

Step 4:

y(−z+2)=0

Step 5:

y(−z+2)

−z+2

=

0 /−z+2

User Cristopher
by
5.5k points
1 vote

Answer:

Z = 2

Explanation:

First, distribute the terms on the left side of the equation.

3(3y - 6) = 7y - 18 + Zy

9y-18=7y-18+Zy, Next add 18 to both sides

9y = 7y+Zy, Subtract 7y from both sides

2y = Zy, Divide both sides by y

2 = Z, Z=2

User Derevo
by
5.2k points